STRENGTH ANALYSIS OF CONTAINER DECK CONSTRUCTION MV. SINAR DEMAK EFECT OF CHARGES CONTAINER USING FINITE ELEMENT METHOD - Mulyatno, Imam Pujo; Arswendo A, Berlian; Alif Maulana, Rachmat (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2012)
Abstract MV. Sinar Demak is a type container ship owned PT Samudera Shipping Services. This ship can used container up to 265 teuâ€™s. on his voyage the ship requires condition of ship is safe, especially in the construction structure. This indicates there are loads working on container deck, in operation would cause problems such as deformation, crack, and other problems. In this final project will analyze maximum stress that occur on container deck MV. Sinar Demak with the help of numerical programe FEM software. This analysis is used a static load analysis to determine of characteristics, location of the largest stress and safety factor of container deck construction structure based on variation of the condition state of vessel. The result using numerical programe FEM software obtained maximum stress on the container deck construction structure on sagging condition is 247 N/mm2 at node 89696 at the frame no 23. Safety factor is true for all condition, safety factor to still water condition is 2,17 forÂ  criteria of materials and 1,55 for BKI standard, safety factor for hogging condition is 2,17 for criteria of materials and 1,55 for BKI standard, and safety factor for sagging condition is 1,61 for criteria of materials and 1,157 for BKI standard.